Cyclic Behavior of Steel Beam to CFT Column Connections with Gusset Plates - Peng Wang; Zhan Wang; Jianrong Pan; Yanjun Zheng; Deming Liu (Advances in Civil Engineering)
Beam-brace-CFT (concrete-filled tubular) column connections provide excellent performance in resisting seismic loads in high-risk areas. However, the load transmission mechanism of this type of connection still remains unclear, and there is a lack of study on it. Therefore, in this paper, the mechanical behavior of beam-brace-CFT column (BBC) connections penetrated by gusset plates was evaluated through experiments and finite element analysis to resolve this issue. The failure modes, strength, stiffness, ductility, and energy dissipation of this type of connection were studied. Experiment results indicated that the gusset plates in BBC (beam-brace-CFT) connections could effectively move the plastic hinge on beam away from the column face, reduce the strain concentration between the beam end and column face, and notably improve the hysteretic behavior; the plastic rotation was able to achieve at least 4% story drift angle before 20% strength degradation. Numerical studies were carried out and validated by experiment results, and then the influence of the weld length and strengthening methods were investigated; some improvement of design suggestions was proposed.